2010
DOI: 10.1089/fpd.2009.0389
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Up Seed Decontamination Process to InactivateEscherichia coliO157:H7 andSalmonellaEnteritidis on Mung Bean Seeds

Abstract: A majority of the seed sprout-related outbreaks have been associated with Escherichia coli O157:H7 and Salmonella spp. Therefore, it is necessary to find an effective method to inactivate these microorganisms on the seeds before sprouting. When treatment with hot water at 85 degrees C for 40 sec followed by dipping in cold water for 30 sec and soaking into chlorine water (2000 ppm) for 2 h was performed, no viable pathogens were found in the enrichment medium and during the sprouting process. The germination y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This was followed by a combination study with reduced hot water temperature and time, followed by soaking in chlorine. In that study 4 , we reported that hot water treatment at 85°C for 40 seconds followed by dipping in cold water for 30 sec and soaking in 2000-ppm chlorine water could achieve complete elimination of E. coli O157:H7 and Salmonella Enteritidis in mung bean seeds without affecting the germination yield after the treatment. Finally, we evaluated the scale-up study results 3 with an actual pasteurization machine (SB-1300: Daisey Mechinary Co. Ltd) for disinfecting food poisoning bacteria, E. coli O157:H7, Salmonella, and non-pathogenic E. coli as a surrogate for practical tests.…”
Section: Successful Seed Decontamination Methodsmentioning
confidence: 99%
“…This was followed by a combination study with reduced hot water temperature and time, followed by soaking in chlorine. In that study 4 , we reported that hot water treatment at 85°C for 40 seconds followed by dipping in cold water for 30 sec and soaking in 2000-ppm chlorine water could achieve complete elimination of E. coli O157:H7 and Salmonella Enteritidis in mung bean seeds without affecting the germination yield after the treatment. Finally, we evaluated the scale-up study results 3 with an actual pasteurization machine (SB-1300: Daisey Mechinary Co. Ltd) for disinfecting food poisoning bacteria, E. coli O157:H7, Salmonella, and non-pathogenic E. coli as a surrogate for practical tests.…”
Section: Successful Seed Decontamination Methodsmentioning
confidence: 99%
“…This treatment was effective for reducing pathogens to below detectable levels after 24 h of enrichment and maintained 95% sprout yield after 72 h. However, treatment at higher water temperature for a shorter times was not as effective (10). Because recovery of injured cells often increases and germination is altered when the treatment sample size increases, this method was further validated on a commercial scale with a 300-kg sample (9). However, when tested on mung bean seeds from a different source, the combination treatment achieved > 5 log CFU/g reduction but was not able to completely eliminate Salmonella from detection (118).…”
Section: Physical Interventions: Thermal Inactivationmentioning
confidence: 99%
“…The survival of E. coli O157:H7 was confirmed according to Bari et al (2010). The homogenized mixture of 10 g of seeds with 90 mL of peptone water in a stomacher bag was kept in an incubator at 378C for 24 h for enrichment, and the homogenates (0.1 mL) were plated onto TSAR and SMACR.…”
Section: Detection Of Surviving Pathogens In Treated Seedsmentioning
confidence: 99%